Effect of modified method of autonomic nervous system activity assessment on results of heart rate variability analysis - Michal Botek; Jakub Krejčí; Filip Neuls; Jiří Novotný (Palacky University, 2013)
BACKGROUND: Quickness and simplicity of examining procedures belong to the key criteria of decision-making process whether the spectral analysis of heart rate variability (SA HRV) would be implemented into the sports training routine as a diagnostic tool. OBJECTIVE: The main aim of this study was to find out how results of the SA HRV are influenced when reducing duration of the first position of standardized orthoclinostatic maneuver (supine–standing–supine) from 5 minutes to 60 seconds. METHODS: The sample consisted of 28 healthy persons divided into two groups (G1 – n = 14, 7 males and 7 females aged 19 to 23; G2 – n = 14, 9 males and 5 females aged 17 to 22). The G1 underwent the autonomic nervous system (ANS) activity assessment firstly by the modified procedure and consecutively by the standard procedure. This order was reversed in the G2. The ANS activity was represented by both, individual HRV parameters and complex indices of the SA HRV. RESULTS: When comparing the standard and modified procedure of the ANS assessment, no significant differences in any of the assessed parameters of the HRV were found. The correlation analysis that the results of the SA HRV indices between both measures of the ANS are highly related was found. This dependence was also present in a majority of the individual HRV parameters. CONCLUSIONS: According to the results of this research, the time-modified method of the ANS assessment provides results of the SA HRV which are comparable to the traditionally applied orthoclinostatic maneuver.